Membumikan Kepemimpinan Kristen Anti Kritik dalam Nilai Etis Kristiani - Yonatan Alex Arifianto (Institut Agama Kristen Negeri Kupang, 2023)
The development of the times in the country's leadership alone cannot be separated from social criticism which is inserted in the creator's content messages in the form of jokes or poetry or also parodies of songs as a form of resistance to the arbitrariness of the authorities. This article aims to instill anti-critical Christian leadership in Christian ethical values which can be the answer for Christian leaders to dedicate themselves to being in servant leadership. Using a descriptive qualitative method with a literature study approach where the Bible is the primary source, it can be concluded that grounding anti-critical Christian leadership in Christian ethical values is first, leaders can clearly understand the Nature of Good Leadership in Christian Leadership based on Christian ethical values. This becomes the foundation and basis for actualizing leadership with the character of Servant leadership, so Anti-Criticism is something that can be well received and of course it is in line with the values and responsibilities of leadership based on the Bible. Therefore, called believers are expected to be able to instill anti-criticism Christian leadership in Christian ethical values so that they have leadership attitudes and responsibilities in the Circle of Criticism that can be dedicated to church ministry and ministry holistically.